The Functional Coloring Signs in the Public and Residential Buildings (Worldwide Experiments – Latakia Facts and Propositions ) - Kassab, Ahmad Said (Latakia University Journal -Engineering Sciences Series, 2019)
أجريت هذه الدراسة، لرصد الوظيفة اللونية في الكتل السكنية والعامة في مدينة اللاذقية وفق القطاع أو الجهة الدارسة، وطبيعة الحلول المقترحة والمنفذة، وبالنظر إلى قدرة اللون، وإمكانية تسخير هذه القدرة للوصول إلى تناغم شكلي ووظيفي ، بالعلاقة مع حجم وتشكيل المبنى (كحالة ذاتية)، وضمن المحيط المجاور (كحالة تخطيطية عامة). ومع الأخذ بعين الاعتبار التجارب العالمية المتقدمة في هذا السياق ،فإننا نلحظ أن اللون لدينا لا يدخل فعليا ًفي عداد الحلول الوظيفية المعمارية المساعدة، ويتصف إن وجد (بالعفوية والبدائية)، وتظهر أهمية البحث في سبر الحالة اللونية الراهنة قدر الإمكان، واستقراء الأساليب الناجعة لتقويمها، واقتراح بعض التوصيات التي تساعد في تنمية دور اللون، وإدماجه لتحقيق الوظيفة المعمارية والعمرانية المرجوة. This research has been done to observe the coloring function of the housing and popular masses in the city of Latakia according to the studying party, and the nature of the executed and suggested solutions and to Look at the color ability and the possibility of exploiting such ability to reach a functional and shaping harmony in relation to the size and the shape of the building (as a self-state) within the nearby surrounding (as a general planning state ). Taking into consideration the worldly advanced experiments in this field, we notice that the color in our works does not actually exist within the scope of the assisting architectural functional solutions. If found, the color is described as being spontaneous and primitive. The importance of this research is manifested in probing the current coloring state as much as possible, and in scrutinizing the effective methods in order to adjust them. Besides, suggesting some recommendations that help in developing the role of the color and amalgamating it to achieve the desired housing and architectural function.